Development and Standardization of Tilapia (Oreochromis niloticus) Fish Fingers Fortified with Moringa Leaves Powder - Kamble, P. A.; Sawant, S. S.; Desai, A. S.; Pathan, D. I.; Wasave, S. M.; Gore, S. B.; Koli, J. M.; Vishwasrao, V. V.; Bhaladhare, D. R. (International Journal of Bio-resource and Stress Management, 2025)
The investigation was conducted during the period of November, 2024 to January, 2025 at the Department of Fish Processing Technology and Microbiology, College of Fisheries, Ratnagiri, Maharashtra, India to develop and standardize the recipe for fish fingers fortified with moringa leaves powder. Nile tilapia (Oreochromis niloticus) contained protein, vitamins, minerals and essential fatty acids. Tilapia was high in polyunsaturated fatty acids (PUFA), particularly the Omega-3 PUFA namely eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA). These nutrients were all essential for the nutritional stability of humans. Tilapia was odourless and lean fish which made it potentially perfect raw material for making ready-to-eat fish products. The yield of fish mince from whole tilapia was 33.91%. The "drumstick" or "horseradish" tree, Moringa (Moringa oleifera), belonged to the Moringaceae family. It was a readily available source of essential nutrients and nutraceuticals that might help to prevent malnutrition. Moringa leaf flour was high in nutrients and contained four times the calcium of milk, 25 times the iron of spinach, six times the zinc of almonds, and twice the protein of yogurt, which might help to combat malnutrition. For the preparation of fish fingers fortified with moringa, various treatments were formulated viz., Fish meat, moringa leaves powder and potato. The fish fingers were prepared with standardized quantity of fish meat (25.36%), moringa leaves powder (0.97%) and potato (24.39%).